THERMAL PERFORMANCE OF TRADITIONAL HOUSE UMA KBUBU - Rini Nugrahaeni; I Ketut Suwantara (Pusbindiklat - LIPI, 2012)
This study identified thermal performances of Uma Kbubu in Maslete village, which include the characterof thermal building and thermal comfort of occupants. Thermal values was measured by Hioki data Logger, Thermocoupletype T, Questemp 34, Anometer Kanomax, and closed questioner to get thermal responsed of occupants.Data was analysed by linear regression and comparation of building’s thermal characteristic between rainy anddry season. Study shows that Uma Kbubu has good thermal performance in rainy and dry season, and capableof creating thermal comfort for its occupants. Roof as building envelope has significant influence to thermalperformance of Uma Kbubu, while the wall had no significant effect. Neutral temperature was 24,6oC on rainyseason and 27,6 oC on dry season.